The impact of health literacy on health-promoting lifestyle among community residents: the chain-mediating role of family health and physical activity - Ma, Yunxia; Huang, Li; Tian, Haodong; Liu, Haowei; Yu, Hanglin; Li, Hansen; Guo, Liya (Frontiers in Psychiatry, 2024)
BackgroundAdopting health-promoting lifestyle (HPL) is crucial for improving overall well-being and reducing the risk of chronic diseases. The relationship between health literacy (HL) and HPL among Chinese community residents is complex, with potential mediating factors yet to be fully understood. Family health and physical activity (PA) may play significant roles in this relationship. This study aims to construct a chain mediation model to explore whether family health and PA mediate the effects of HL on HPL in Chinese community residents.MethodsUsing the convenient sampling method, 1,072 Chinese community residents were selected for a cross-sectional study. All participants completed a self-report questionnaire that collected demographic information, as well as data from the Health Literacy Scale Short-Form (HLS-SF12), Family Health Scale Short-Form (FHS-SF), Physical Activity Rating Scale (PARS-3), and Health Promoting Lifestyle Profile-II Revise (HPLP-II R). Data were analyzed using SPSS 26.0, with mediation analysis performed using the SPSS PROCESS macro.ResultsThere were significant pairwise correlations between HL, family health, PA, and HPL (p < 0.01). HL was directly linked to HPL (effect = 0.442; SE = 0.025; 95% CI: 0.392, 0.491). Additionally, three indirect pathways were identified: family health independently mediated 6.02% of the effect (effect = 0.032; SE = 0.010; 95% CI: 0.013, 0.051), PA also independently mediated 9.02% of the effect (effect = 0.048; SE = 0.010; 95% CI: 0.030, 0.068), and a combined chain mediation through both family health and PA accounted for 1.88% of the effect (effect = 0.010; SE = 0.003; 95% CI: 0.005, 0.017).ConclusionHL not only has a direct impact on promoting HPL but also influences it indirectly through the mediating roles of family health and PA. These insights elucidate the mechanisms by which HL affects HPL, providing valuable theoretical guidance for the development and implementation of effective strategies to encourage healthy lifestyle practices.